2008
DOI: 10.1002/dvdy.21764
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two Mst1‐deficient mouse models

Abstract: Mammalian sterile 20-like kinase 1 (Mst1) is a ubiquitously expressed serine/threonine kinase belonging to the family of Sterile 20-like kinases. MST1 has been inferred to play important roles in apoptosis and in the inhibition of proliferation in mammalian cells. Here, we describe the genetic characterization of Mst1-deficient mice produced by two distinct gene-trap insertions. Animals generated from clone RRT293 exhibit transmission ratio distortion favoring the mutated allele and is amplified with each gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…MST1 inhibits YAP activation and acts as a tumor suppressor 12 . Genetic knockout MST1 results in hyperactivation of YAP and tumorigenesis 15,51 . How MST1 exerts its tumor suppressor function in human cancer remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MST1 inhibits YAP activation and acts as a tumor suppressor 12 . Genetic knockout MST1 results in hyperactivation of YAP and tumorigenesis 15,51 . How MST1 exerts its tumor suppressor function in human cancer remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Genetic knockout MST1 results in hyperactivation of YAP and tumorigenesis. 15 , 51 How MST1 exerts its tumor suppressor function in human cancer remains largely unknown. Previous study has shown that MST1 promotes cancer growth by inhibiting AMPK‐SIRT3 mediated mitochondrial fission for cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of the Mst1 and Mst2 promoters have been shown to inhibit the WW45-Rassf1-Mst pathway in human sarcomas [48] and loss of cytoplasmic Mst1 has been reported to be a marker for tumor progression in colorectal cancer, suggesting that Mst1 can function as a tumor suppressor [49]. However, the Mst1 knockout mouse is reported to have a surprisingly mild phenotype and does not appear, on its own, to have tumor suppressor function [25,50]. Whether Mst2, which can replace Hippo function in flies, will have such activity is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Since MST and LATS have significant effects on the living organism, they are only epistatically associated with YAP. 58 , 59 , 60 , 61 , 62 , 63 , 64 One of the conserved proteins in the Hippo pathway is the Ajuba Scaffold protein, which interacts with LATS kinases and SAV, limiting centromere signaling and decreasing inhibition of YAP phosphorylation. 65 EFGR-RAS signaling activates MAPKs (ERK and JNK), both of which MAPKs phosphorylate Ajuba proteins, increase LATS binding, and YAP transcriptional activation.…”
Section: Hippo Pathwaymentioning
confidence: 99%